Autism and diagnostic substitution: evidence from a study of adults with a history of developmental language disorder. - Bishop, D; Whitehouse, A; Watt, H; Line, E (2008)
Rates of diagnosis of autism have risen since 1980, raising the question of whether some children who previously had other diagnoses are now being diagnosed with autism. We applied contemporary diagnostic criteria for autism to adults with a history of developmental language disorder, to discover whether diagnostic substitution has taken place. A total of 38 adults (aged 15-31y; 31 males, seven females) who had participated in studies of developmental language disorder during childhood were given the Autism Diagnostic Observation Schedule--Generic. Their parents completed the Autism Diagnostic Interview--Revised, which relies largely on symptoms present at age 4 to 5 years to diagnose autism. Eight individuals met criteria for autism on both instruments, and a further four met criteria for milder forms of autistic spectrum disorder. Most individuals with autism had been identified with pragmatic impairments in childhood. Some children who would nowadays be diagnosed unambiguously with autistic disorder had been diagnosed with developmental language disorder in the past. This finding has implications for our understanding of the epidemiology of autism.